Influence of rainfall on transient seepage field of deep landslides: A case study of area II of Jinpingzi landslide. Issue 2 (October 2020) - Jing, Fu; Ling, Huang Shu; Xiuli, Ding; Jinlong, Wang
Abstract: Rainfall is one of the primary factors that induce landslides. Rainfall infiltration forms a transient seepage field in slopes, thereby leading to an increase in water content, a decrease in matric suction, and an increase in the volume weight of slopes. The increase in water content in rock and soil leads to the degradation of the mechanical properties of the slope medium and reduces the shear strength, thus causing slope instability. In this study, a large-scale accumulation landslide is taken as the research object. The front edge of the landslide is high and is not eroded by river water. Hence, rainfall is regarded as the main external factor that changes the groundwater and seepage field of the landslide. According to the landslide's topography, geological data, local rainfall, and hydrological monitoring results, the saturated–unsaturated seepage theory of rock and soil and the finite difference method are used to analyze the impact of rainfall on the landslide's seepage field and groundwater. The evolution law of the transient seepage field of the landslide under the condition of rainfall duration is studied. The results provide a basis for the analysis of landslide deformation and stability.